MCMI-III Personality Complexity and Depression Treatment Outcome Following Group-Based Cognitive–Behavioral Therapy - Craigie, Mark; Saulsman, L.; Lampard, Amy (John Wiley & Sons, 2007)
This study investigated the association of personality disorder complexity to treatment outcome for depression following time-limited group-based cognitive–behavioral therapy. One hundred fifteen outpatients with a primary diagnosis of depression participated in the study. In this study, personality disorder complexity was determined by the degree of personality disorder comorbidity identified by the Millon Clinical Multiaxial Inventory-III (T. Millon, 1994). As predicted, analyses revealed that increasing personality disorder complexity was related to increasing baseline symptom severity and slightly poorer end-state functioning at posttreatment. However, results regarding clinically significant improvement and mean improvement in depression symptoms were less supportive of an association between personality disorder complexity and poorer treatment outcome. The implications of these findings for treatment planning are discussed.